ESTIMASI SERAPAN KARBON PADA SUBSTRAT DASAR BERDASARKAN TUTUPAN LAMUN EKOSISTEM PADANG LAMUN DI PULAU BARRANG LOMPO KOTA MAKASSAR PROVINSI SULAWESI SELATAN - Asbar Asbar; Muhammad Yunus (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
The purpose of this study was to determine seagrass cover and carbon estimation in seagrass ecosystems on Barrang Lompo Island, South Sulawesi Province by using the quadratic transect method (perpendicular to the shoreline). The research was carried out in July-August 2022. Located on Barrang Lompo Island. Sample analysis was carried out at the Chemistry and Soil Fertility Lab, Hasanuddin University. The method used in this study for seagrass cover on Barrang Lompo Island was a quadratic transect (perpendicular to the shoreline) modified from the Seagrass Watch method. The consideration of choosing Seagrass Watch as a reference is that this method is suitable for monitoring activities carried out by the general public or volunteers because the implementers of seagrass monitoring in COREMAP - CTI activities are not only researchers or technicians in the seagrass field. The method used for sampling the substrate is purposive sampling method. Purposive sampling is a sampling technique with certain considerations. The results showed that the seagrass cover on Barrang Lompo Island was in the medium category with an average cover value of 37.05% and the total organic carbon content of the substrate contained in one area was 0.70 Ton/Ha with a total CO2 absorption on the substrate of the field. Seagrass in Barrang Lompo waters is 2.57 Ton/Ha.